A Coverage Hole Healing Strategy with Awareness of Data Delivery Time in Wireless Sensor Networks. (25th December 2013) - Lin, Fu-Tian; Sung, Tien-Wen; Yang, Chu-Sing
Abstract : An efficient wireless sensor network (WSN) should maintain full sensing coverage and topology connectivity within its sensing field. Once holes occur due to failed sensors, the functionality and performance of the WSN will be affected. In this work, the proposed hole healing strategy aims to shorten the delivery hop count by a dynamic hole healing process in order to improve the data delivery time while maintaining the coverage ratio and topology connectivity. The criteria used to determine which hole should have the highest priority for healing in the next round include the weighted distance, angle magnitude, and depth of the hole. This study proposes a mobile robot, operating within the WSN, which carries redundant sensors to patch the holes by an optimum healing path. This path is determined based on the proposed EDPS (equally divided path selection) algorithm. Simulation results show the superiority of the proposed hole healing scheme over other general methods.